Cytotoxic effects of Etlingera pavieana rhizome on various cancer cells and identification of a potential anti‐tumor component. Issue 4 (8th March 2018) - Iawsipo, Panata; Srisook, Ekaruth; Ponglikitmongkol, Mathurose; Somwang, Tatiyar; Singaed, Onanong
Abstract: Much effort over the last several decades has been made to identify new anticancer agents, preferably with reduced adverse side effects. In this study, cytotoxic activity of rhizome extract from Etlingera pavieana (Pierre ex Gagnep.) R.M.Sm. was assessed. We demonstrate that ethanolic extract (EE) of E. pavieana rhizome shows reduced viabilities of several cancer cell lines in dose‐ and time‐dependent manners. Following cytotoxic‐guided isolation of EE, the bioactive compound trans ‐4‐methoxycinnamaldehyde (4‐MCA) was identified. 4‐MCA exhibited a dose‐dependent inhibitory effect on cancer cell growth with the IC50 values ranging from 34 to 40 µM, which are approximately four times lower than that of noncancerous cells. This antiproliferative effect might be due to its cooperative actions of inducing apoptosis and arresting cell cycle at G2/M phase. To the best of our knowledge, this is the first report on the in vitro antitumor promoting activity of 4‐MCA. Practical applications: Rhizome of E. pavieana (Zingiberaceae) has been widely used as spices and a medicinal plant in Thailand, Cambodia, Laos, and Vietnam. In this study, we demonstrated the medicinal role of this plant on suppressing the growth of various cancer cells of common cancer types including those of breast, cervix, liver, and colon/rectum. Moreover, we verified that this action was, at least in part, due to one of its constituents, 4‐MCA. Overall results demonstrated the potential cytotoxic activities of 4‐MCA toward cancer cells, including inhibition of cell proliferation and colony formation, induction of apoptosis, and cell cycle arrest whereas it exhibited negligible effect on noncancerous cells. The comprehensive characterization of E. pavieana rhizome performed in this study, highlights the pharmaceutical potential of 4‐MCA, one of its major constituents, to be a promising candidate for future development of new cancer regimen.